Synthesis of NiSe2/Fe3O4 Nanotubes with Heteroepitaxy Configuration as a High‐Efficient Oxygen Evolution Electrocatalyst. Issue 7 (1st May 2022) - Jiang, Xin; Xie, Qifan; Lu, Gongxun; Wang, Yao; Liu, Tiefeng; Liu, Yujing; Tao, Xinyong; Nai, Jianwei
Abstract: The rational design of high‐efficient non‐noble metal electrocatalysts for oxygen evolution reactions (OER) is of significance in electrochemical energy conversion. However, such low‐cost but highly active electrocatalysts remain poorly developed because of the daunting synthetic challenge. Here, the synthesis of NiSe2 /Fe3 O4 nanotubes via a facile self‐templating strategy, which manifests unique tetragonal morphology, asymmetric hollow interior, and unusual but adaptable heteroepitaxy structure, is reported. Benefiting from sufficient active sites and their improved activity around the heterointerface, accompanied by the good conductivity, the NiSe2 /Fe3 O4 nanotubes exhibit as a superior OER electrocatalyst, which affords the current density of 10 mA cm −2 at a very small overpotential of 199 mV, high attainable current density beyond 200 mA cm −2, and mass activity of 984.5 A g −1, as well as excellent stability for 100 h in the alkaline media. This work provides a unique synthetic pathway to fabricate superior OER electrocatalysts by optimizing their composition and architecture. Abstract : NiSe2 /Fe3 O4 nanotubes with unique tetragonal morphology, asymmetric hollow interior, and unusual but adaptable heteroepitaxy structure are constructed by a facile self‐templating method. Benefiting from the synergistic effect between the two components and the electronic regulation mediated by the heterointerface, the as‐formed NiSe2 /Fe3 O4 nanotube catalyst exhibits excellent electrocatalytic oxygen evolution performance.